Valoración de las sanciones alternativas a la privación de libertad en las contravenciones de tránsito - Andrade Moncayo, Michael Fred (2021)
This research work is entitled: ASSESSMENT OF THE ALTERNATIVE SANCTIONS TO THE DEPRIVATION OF FREEDOM IN TRANSIT CONTRIBUTIONS and arises before the problematic that we synthesize in the scientific problem that we pose thus: In the assumption that the COIP, establish the legal possibility of applying alternative penalties to the deprivation of liberty in the case of the traffic violation provided for in art. 383 of the COIP, could the principles of minimum criminal intervention, exceptionality of deprivation of liberty, proportionality and necessity in the application of punishment be guaranteed more effectively? The need for this investigation arises from the fact that traffic violations are minor offenses, which, in addition to being contraventional, are also based on reckless actions that, therefore, merit administrative treatment and, in case the legislator understands that being part of the Criminal Law, then, the sanctions to be applied should be less burdensome, afflictive and invasive, with all of which the due process and the minimum intervention of the Criminal Law would be guaranteed, as ...........